1999
DOI: 10.1093/oxfordjournals.pcp.a029515
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteins and Protein Kinase Activities Intrinsic to Inner Membranes of Potato Tuber Mitochondria

Abstract: Inside-out submitochondrial particles (IO-SMP) were isolated and purified from potato (Solarium tuberosum L. cv.) tubers. When these IO-SMP were incubated with [y-32 P]ATP more then 20 proteins became labelled as a result of phosphorylation. The 32 P incorporation was stimulated by the oxidising reagent ferricyanide. Except for a 17 kDa protein which was phosphorylated only in the absence of divalent cations, the protein phosphorylation required Mg 2+ . The time for half-maximum 32 P incorporation was 4 min fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Phosphorylation of the E1α subunit of the branched‐chain α‐ketoacid dehydrogenase and the 18 kDa IP subunit of complex I [7] has so far only been detected in mammalian mitochondria. However, there are clearly more phosphoproteins present since labelling of intact mitochondria or submitochondrial fractions gives up to 30 labelled bands on one‐dimensional (1D) gels [8–11].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of the E1α subunit of the branched‐chain α‐ketoacid dehydrogenase and the 18 kDa IP subunit of complex I [7] has so far only been detected in mammalian mitochondria. However, there are clearly more phosphoproteins present since labelling of intact mitochondria or submitochondrial fractions gives up to 30 labelled bands on one‐dimensional (1D) gels [8–11].…”
Section: Introductionmentioning
confidence: 99%
“…Incubating intact mitochondria (3)(4)(5) or submitochondrial fractions like the outer membrane (6) or the inner membrane (7)(8)(9) with [␥- 32 P]ATP gives labeling of up to 30 proteins (as detected by one-dimensional gel electrophoresis) indicating that kinases are present in these fractions and in contact with target proteins. The matrix appears to contain one of more protein phosphatases responsible for dephosphorylation of inner membrane phosphoproteins (8,9).…”
mentioning
confidence: 99%
“…1B) showed that the polypeptide and phosphoprotein patterns were quite different. The labelling time was only 2 min, the time giving half‐maximal phosphorylation [11] to maximize the sensitivity to inhibition, resulting in somewhat less 32 P incorporation than in subsequent experiments (cf. Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Protein phosphorylation assays were carried out in a volume of 50 μl containing 250 μg IO‐SMP proteins [11]. Final concentrations in the reaction mixture were as follows: 0.3 M sucrose, 50 mM HEPES–KOH (pH 7.5), 5 mM MgCl 2 , 0.1 mM CaCl 2 and 0.2 mM (0.4–1.0 Ci mmol −1 ) [γ‐ 32 P]ATP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation